Searching for additional functions of fish hemoglobins: evidence of multiple quaternary structures and exogeneous coordination states - VERGARA, ALESSANDRO; MERLINO, ANTONELLO; L. Vitagliano; G. Barbiero; C. Verde; G. di Prisco; Lelio Mazzarella (country:DNK, 2008)
All fish hemoglobins (Hb) show a high auto-oxidation rate, and some fish Hbs are endowed with Root effect (drastic drop of cooperativity at acidic pH). Differently from temperate fish Hbs, at physiological pH Antarctic fish Hbs (AFHbs) in the ferric state show both an aquomet form and two distinct hemichromes within a R / T intermediate quaternary structure (1). Interestingly, AFHbs exhibit a peroxidase activity higher than that observed for mammalian and temperate fish Hbs, thus suggesting that a partial hemichrome state in tetrameric Hbs does not protect them from peroxidation as previously proposed (2). At acidic pH, a combined EPR / x-ray crystallography approach has revealed, only for Root-effect AFHbs, significant amount of pentacoordinated (5C) high-spin Fe(III) species.(3) Furthermore, along the oxidation pathway, a combined x-ray crystallography / Resonance Raman spectroscopy of AFHbs has revealed a hybrid valence state [α(O2)/β(Fe3+, pentacoordinate)].(4) This valence hybrid states prompted us to test a FeSOD activity, that is as low as human Hb. A combined x-ray crystallography / FT-IR study has revealed at least two coordination states of the carbomonoxy form of AFHbs, one corresponding to a His assisted CO binding (band III at 1951 cm-1), and another to a not-His assisted CO binding (band IV at 1968 cm-1). The band IV, typical of both temperate fish (carp and trout) Hbs and AFHbs, assigned to the second CO coordination state, justifies the high auto-oxidation rate of fish Hbs. Furthermore, this novel CO coordination in AFHb occurs within a R-T intermediate quaternary structure. These findings provide an alternative structural explanation of the Root effect, in terms of a three state model .(5) This work was financially supported by PNRA (Italian National Programme for Antarctic Research) 1. Vergara, A., Franzese, M., Merlino, A., Vitagliano, L., di Prisco, G., Verde, C., Lee, H. C., Peisach, J., and Mazzarella, L. (2007) Biophys. J. 93, 2822-2829 2. Feng, L., Zhou, S., Gu, L., Gell, D., Mackay, J., ...